2018
DOI: 10.1159/000492331
|View full text |Cite
|
Sign up to set email alerts
|

X-Aptamer Technology Identifies C4A and ApoB in Blood as Potential Markers for Schizophrenia

Abstract: The field of proteomics is rapidly gaining territory as a promising alternative to genomic approaches in the efforts to unravel the complex molecular mechanisms underlying schizophrenia and other psychiatric disorders. X-aptamer tech­nology has emerged as a novel proteomic approach for high-sensitivity analyses, and we hypothesized that this technology would identify unique molecular signatures in plasma samples from schizophrenia patients (n = 60) compared to controls (n = 20). Using a combinatorial library o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Ten studies reported C4 concentrations, of which two found significantly increased levels in cases ( Laskaris et al, 2018 ; Walss-Bass et al, 2019 ), one found significantly decreased levels in cases ( Ji et al, 2019 ) and seven studies found no significant difference ( Ali et al, 2017 ; Fontana et al, 1980 ; Idonije et al, 2012 ; Maes et al, 1997 ; Santos Soria et al, 2012 ; Spivak et al, 1993 ; Spivak et al, 1989 ). One of these studies stratified cases by medication status ( Maes et al, 1997 ) and found increased serum C4 in drug-free patients compared to controls without schizophrenia ( Maes et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies reported C4 concentrations, of which two found significantly increased levels in cases ( Laskaris et al, 2018 ; Walss-Bass et al, 2019 ), one found significantly decreased levels in cases ( Ji et al, 2019 ) and seven studies found no significant difference ( Ali et al, 2017 ; Fontana et al, 1980 ; Idonije et al, 2012 ; Maes et al, 1997 ; Santos Soria et al, 2012 ; Spivak et al, 1993 ; Spivak et al, 1989 ). One of these studies stratified cases by medication status ( Maes et al, 1997 ) and found increased serum C4 in drug-free patients compared to controls without schizophrenia ( Maes et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four articles were excluded for multiple reasons (detailed in Fig. 1 ) resulting in 24 included studies ( Ali et al, 2017 ; Boyajyan et al, 2010 ; Cazzullo et al, 1998 ; Foldager et al, 2012 ; Fontana et al, 1980 ; Hakobyan et al, 2005 ; Hong et al, 2016b ; Idonije et al, 2012 ; Ji et al, 2019 ; Kucharska-Mazur et al, 2014 ; Laskaris et al, 2018 ; Li et al, 2016 ; Li et al, 2012 ; Maes et al, 1997 ; Mayilyan et al, 2006 ; Mayilyan et al, 2008a ; Ramsey et al, 2013 ; Santos Soria et al, 2012 ; Sasaki et al, 1994 ; Schwarz et al, 2012 ; Spivak et al, 1993 ; Spivak et al, 1989 ; Walss-Bass et al, 2019 ; Wong et al, 1996 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma levels of Complement 4a protein are increased in Alzheimer's disease [19]. X-Aptamers identi ed C4A and ApoB as potential markers for schizophrenia from blood [20]. Complement and microglia cells of the innate immune system mediate early synapse loss in a mouse model of Alzheimer's dementia [21].…”
Section: Introductionmentioning
confidence: 99%